Update for Advance CAR-T Therapy in Solid Tumors, Clinical Application in Peritoneal Carcinomatosis From Colorectal Cancer and Future Prospects - Qian, Siyuan; Villarejo-Campos, Pedro; Guijo, Ismael; Hernández-Villafranca, Sergio; García-Olmo, Damián; González-Soares, Sara; Guadalajara, Héctor; Jiménez-Galanes, Santos; Qian, Cheng (Frontiers in Immunology, 2022)
Latest advances in the field of cancer immunotherapy have developed the (Chimeric Antigen Receptor) CAR-T cell therapy. This therapy was first used in hematological malignancies which obtained promising results; therefore, the use of CAR-T cells has become a popular approach for treating non-solid tumors. CAR-T cells consist of T-lymphocytes that are engineered to express an artificial receptor against any surface antigen of our choice giving us the capacity of offering precise and personalized treatment. This leaded to the development of CAR-T cells for treating solid tumors with the hope of obtaining the same result; however, their use in solid tumor and their efficacy have not achieved the expected results. The reason of these results is because solid tumors have some peculiarities that are not present in hematological malignancies. In this review we explain how CAR-T cells are made, their mechanism of action, adverse effect and how solid tumors can evade their action, and also we summarize their use in colorectal cancer and peritoneal carcinomatosis.